SISTEM AKUNTANSI PEMBELIAN BBM PADA SPBU 14.2856118 HJ. ROSNIATI KECAMATAN RAMBAH SAMO - Is, Fitriyati (E-Journal Cano Ekonomos, 2013)
The system is a network of prosedures estabilished by pattern are integrated to perform basic activities of the company. While the procedure is a sequence pf clerical activity, usually involving mutlriple people within a departement or more, whice are made to ensure the compnyâs handling of the transactions that occur over and over again.Purchase an activity that is often done to meet the needs of the compannyâs stock.The purchase is a transaction entered into by the company for goods that can be sold to consumers i order to gain advantage.This research was connducted at the SPBU 14.2856118 Hj. Rosniati Hsb, with field surveys and the interviews of relevant employees. This research uses descriptive method, which compiled the data obtained in such a manner and alalyzed by relevan theory and then drawn conclusions. From the result of this research note purchase accounting systems at the SPBU 14.2856118 Hj. Rosniati Hsb, starting with a letter of request and the purchase of fuel oil required by the manager, which was sent to the administration departement to make purchase order letter as many as 5 (five) copies to be sent to the leadership of SPBU, manager, suppliers, treasury and archives. Then the SPBU waiting for the decision of the supplier as well as the distribution of supplies fuel to the SPBU. Purchase Accounting System at the SPBU 14.2856118 Hj. Rosniati Hsb is still done manually and less neatly arranged.